Frequency of venous thromboembolism during hajj sessions 2017-2019 in Makkah, Saudi Arabia - Nazir, Imran; Al Kalkami, Amna; Elsalamouny, ayed; Elimam, Amal A. A.; Elimam, Amani A. A.; Ezzat, Sadeen E.; Fallatah, Abdul Aziz M. O.; Fatima, Urooj; Mayis, Hussam Saleh; Khalil, Khalid (International Journal of Research in Medical Sciences, 2023)
Background: Venous thromboembolism (VTE) includes deep vein thrombosis (DVT) and pulmonary embolism (PE), both are serious health risks. In western countries, VTE affects about 114 to 184 people per 100,000. Asian populations have a significantly lower incidence than western populations. The true incidence of VTE is still not well documented in Saudi Arabia (KSA). There are different major risk factors especially in hajj season that predispose a person to thrombosis. The mortality rate of autopsy-based pulmonary embolism reaches up to 30%. Methods: This single-centered retrospective descriptive study was done in security forces hospital Makkah, Saudi Arabia during hajj period (30 days) for consecutive three-year. All admitted confirmed DVT and PE patients (N=32) of both genders with age >14 years were included. Patients’ data were extracted from the electronic medical record. Data were analysed by SPSS version 23. Results: Deep venous thrombosis (DVT) was developed in 67.7% while 19.3% of patients suffered from pulmonary embolism (PE) out of a total of 32 subjects. Females were more affected by 18 (56.3%) than males by 14 (43.8%). The mean age of patients was 51.78 years (SD ±16.21). A statistically significant association (p<0.005) between provoked VTE status and age, immobility, and history of surgery was seen. There was no mortality documented in this study. Conclusions: This study provides insights into hajj period hospital admitted patients’ frequency of VTE, changing patient profiles, management strategies, and subsequent outcomes in patients with venous thromboembolism. There is a need for greater awareness of VTE prophylaxis about its prevention, especially in hajj season.